Internalisasi Nilai Ukhuwah Islamiyah dalam Pembentukan Solidaritas Sosial Masyarakat - Mutia Isfah Ardilah; Rosalina Zulhijjah; Ali Maulida (STIT Syekh Muhammad Nafis Tabalong, 2026)
In the modern era, pluralistic societies face major challenges to social cohesion, including ideological polarization, social fragmentation, and an empathy crisis driven by increasing individualism. Islam offers the concept of ukhuwah (brotherhood) as a fundamental sociological pillar for reconstructing and strengthening weakened social solidarity. This study examines ukhuwah Islamiyah as a theological-sociological foundation for building social solidarity and maps its implementation strategies across levels of contemporary society. Using a qualitative library research approach, primary data were drawn from the Qur’an, particularly Surah Al-Hujurat verse 10, and the Hadith of the Prophet Muhammad (peace be upon him), while secondary data came from classical tafsir, Islamic literature, and reputable academic journals. Data were analyzed descriptively, interpretatively, and through content analysis, with source triangulation ensuring validity. The findings show that ukhuwah Islamiyah is not merely a passive theological doctrine, but active social capital encompassing bonding capital within Muslim communities and bridging capital across communities. Sociologically, it manifests in three inclusive dimensions: ukhuwah Islamiyah (Islamic brotherhood), ukhuwah wathaniyah (national brotherhood), and ukhuwah basyariyah (human brotherhood). Its operationalization occurs at three levels: individual, through empathy, mutual assistance, and conflict resolution; social, through collective cooperation and Islamic philanthropy; and educational, through moral value transmission and exemplary conduct. Consistent and systematic strengthening of ukhuwah functions as both a preventive and curative response to modernity’s disruptions and as a strategic foundation for an inclusive, harmonious, and prosperous civil society.